Steel Plate Shear Walls Are Not Plate Girders - Berman, Jeffrey W.; Bruneau, Michel (Engineering Journal, 2004)
Steel plate shear walls that are allowed to buckle in shear and form a diagonal tension field have been the subject of several experimental and analytical studies. In some of these studies, references are made to the physical and analytical similarities between steel plate shear walls and vertical cantilever plate girders. Though these comparisons allow engineers to become quickly familiar with steel plate shear wall concepts in a qualitative way, they have led some to believe that steel plate shear walls can be quantitatively designed using standard plate girder shear strength equations. In this paper, the shear strength of steel plate shear walls found using an accepted model based on plastic analysis, and the shear strength for plate girders calculated from design code equations, are compared with the ultimate strengths of steel plate shear walls obtained from various experimental studies. It is shown that plate girder design equations significantly underestimate the strength of steel plate shear walls, leading to designs with greater-than-expected strength and a breakdown in the capacity design philosophy (i.e. leading to the occurrence of unintended failure modes) as well as an uneconomical use of steel. Strengths calculated from plastic analysis of an accepted analytical model for steel plate shear walls agree well with the experimental studies.